Transport Accessibility In Light Of The DEA Method - Górniak, Joanna (Comparative Economic Research. Central and Eastern Europe, 2014)
The development of transport infrastructure and increasing the efficiency of transport services are major factors of economic growth. The concept of transport accessibility can be analysed in various aspects. This article focuses on the accessibility of freight transport by road and rail, measured with infrastructure equipment. The primary objective of this study is to determine the efficiency of selected European countries in 2000, 2005 and 2010 in terms of transport accessibility for given expenditures and results. The efficiency will be measured with the Data Envelopment Analysis, which assesses the efficiency with which a given economy transforms expenditures into results. The hypothesis assumes the existence of differences between the efficiency in terms of transport accessibility in European countries and a possibility to increase this efficiency by using the experience of countries with a high efficiency level.